Olmesartan Blocks Advanced Glycation End Products-Induced VCAM-1 Gene Expression in Mesangial Cells by Restoring Angiotensin-Converting Enzyme 2 Level - Ishibashi, Y.; Matsui, T.; Yamagishi, S. (Hormone and Metabolic Research, 2014)
Advanced glycation end products (AGEs) and their receptor (RAGE) system are involved in diabetic nephropathy. Angiotensin-converting enzyme 2 (ACE 2) plays a protective role against cardiovascular and renal injury by stimulating the production of angiotensin-(1–7) [Ang-(1–7)], an antagonist of angiotensin II (Ang II). However, effects of the AGEs-RAGE axis on ACE 2 expression in mesangial cells remain unknown. We examined here the role of ACE 2 in the AGEs-RAGE-induced mesangial cell damage and investigated whether olmesartan, one of the Ang II type 1 receptor blockers (ARB), prevented the deleterious effects of AGEs via restoration of ACE 2 and Ang-(1–7) level. AGEs significantly increased superoxide generation, upregulated RAGE mRNA level, and decreased ACE 2 gene expression and Ang-(1–7) production in mesangial cells, all of which were blocked by olmesartan, but not by a different type of ARB, azilsartan. An antioxidant, N-acetylcysteine or RAGE-antibodies also restored the decrease in ACE 2 mRNA level in AGEs-exposed mesangial cells. Moreover, olmesartan, but not azilsartan completely inhibited the AGEs-induced increase in vascular cell adhesion molecule-1 (VCAM-1) mRNA level in mesangial cells, which was abolished by the treatment with A-779, an antagonist of Ang-(1–7) receptor, Mas receptor. Our present study suggests that olmesartan could block the AGEs-induced VCAM-1 gene induction in mesangial cells by restoring the downregulated ACE 2 levels and subsequently stimulating the Ang-(1–7)-Mas receptor axis. Restoration of ACE 2 levels and blockade of renin-angiotensin system by olmesartan might be a promising strategy for the treatment of diabetic nephropathy.
Keywords: AGEs; ACE 2; Ang-(1–7); mas receptor